COMMUNICATION IN FOREIGN LANGUAGES FOR PERSONAL DEVELOPMENT AND PROFESSIONAL CAREER - Vaiciuniene, Vilhelmina; Gedvilas, Paulius (European Scientific Journal, ESJ, 2015)
The European Framework of key competences for lifelong learning, released at the end of 2006, identifies and defines eight competences that everyone needs to acquire in order to achieve personal and professional goals, social inclusion and active citizenship in today’s rapidly-changing world. The paper discusses the results of the pilot study on communication in foreign languages, one out of eight key competences, conducted in 2013. The pilot research was carried out under the project Research and Development Platform for Adult Training of Generic Competences, Measure VP1-3.1-ŠMM-07-K “Support to Research Activities of Scientists and Other Researcher (Global Grant)”. The analysis of the situation in Lithuania pertinent to conceptual understanding of the competence of communication in foreign languages, its development for personal and professional growth and labour market demand is presented. The findings reveal the respondents’ self-evaluation of the competence of communication in foreign languages, the main challenges and opportunities it offers for professional life and career, personal development and participation in civic and community life.